2017
DOI: 10.3892/mmr.2017.7380
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical loading modulates heterotopic ossification in calcific tendinopathy through the mTORC1 signaling pathway

Abstract: Excessive mechanical loading is a major factor affecting heterotopic ossification (HO), which is a major pathological alteration in calcific tendinopathy. However, physical therapies with mechanical loading as the functional element have exhibited promising results in the treatment of calcific tendinopathy. The dual effects that mechanical loading may have on the pathogenesis and rehabilitation of calcified tendinopathy remain unclear. The present study was designed to investigate the effects of mechanical loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Several studies have demonstrated that mechanical loading could activate the mTORC1 signaling pathway via inducing the phosphorylation of p70 S6 kinase ( Lin and Liu, 2019 ). Chen found mechanical loading modulated HO of the tendon through the mTORC1 signaling pathway, furthermore, low elongation mechanical loading attenuated HO, while high elongation mechanical loading accelerated HO in vivo ( Chen et al, 2017 ). Stimulated by mechanistic signaling, mTORC1 activates Sirtuin 1 (Sirt1) in the nucleus.…”
Section: Mechanics and Homentioning
confidence: 99%
“…Several studies have demonstrated that mechanical loading could activate the mTORC1 signaling pathway via inducing the phosphorylation of p70 S6 kinase ( Lin and Liu, 2019 ). Chen found mechanical loading modulated HO of the tendon through the mTORC1 signaling pathway, furthermore, low elongation mechanical loading attenuated HO, while high elongation mechanical loading accelerated HO in vivo ( Chen et al, 2017 ). Stimulated by mechanistic signaling, mTORC1 activates Sirtuin 1 (Sirt1) in the nucleus.…”
Section: Mechanics and Homentioning
confidence: 99%
“…We found that mechanical stretching increased the phosphorylation of S6 and 4E-BP1. Although we did not compare different loads of mechanical stretching in regulation of mTOR pathway, Chen et al shows high elongation mechanical stretching (12%) leads to increased P70S6K (a direct substrate of mTORC1 and kinase for ribosomal protein S6) and subsequent RUNX2 expression in rat tendon cells while low elongation (4%) has opposite effects 31 . Additionally, we revealed increased association of eIF4G protein with the mRNA 5´-terminal cap after mechanical stretching.…”
Section: Discussionmentioning
confidence: 95%
“…These studies support our current results of desloratadine inhibiting the ectopic bone formation of Achilles tenotomy mice model. Desloratadine changed BMP signaling but it may not be the primary mechanism because the mTORC1 signaling pathway is reported to be involved in HO of Achilles tenotomy mice model 23,24 . Further research on this is needed.…”
Section: Discussionmentioning
confidence: 99%